The European Profiling Grid (EPG) Pre-service Teachers’ Level in Lesson and Course Planning Competence - Neni Nurkhamidah (Universitas Muhammadiyah Kalimantan Timur, 2023)
It is recognized that teachers’ quality affects students’ performance. Therefore, the stakeholders have to make sure that teachers have the competence to perform the role as a qualified teacher. English Department of MNC University employs The European Profiling Grid (EPG) to assess preservice teacher competencies. The graduates of this department have to minimally achieve novice teachers’ level of EPG. This study aims at finding the preservice teacher level in lesson and course planning based on EPG standards. The descriptive qualitative method is applied. This research involves 17 students of MNC University in the Praktik Keterampilan Lapangan or Teaching Practice. The data is obtained from the lesson plans developed by preservice teachers and interviews. The result shows that the 13 preservice teachers of the English Department of MNC University are at the level of novice teacher and 4 preservice teachers are at the level of experienced teacher. The result indicates that all of the preservice teachers involved in this research have achieved the minimum requirements of graduates based on EPG, especially in lesson and course planning competence.